The Battle of Iwo Jima began 80 years ago. Listen to recordings from the frontlines - Ulaby, Neda (2025)
The Library of Congress preserved recordings from Marine Corp combat correspondents at Iwo Jima that included interviews with soldiers, music and the sounds of war.
United States of America